Pembungkaman Kaum Perempuan dalam Film Indonesia (Penerapan Teori Muted Group Dalam Film “Pertaruhan”) - Ratna Permata Sari (Program Studi Ilmu Komunikasi, 2014)
Sex and gender are two different concepts. But for women, gender or the inherent nature of the cultural processes that give rise to various inequalities in society such as marginalization, stereotype, violence and negative labeling.This article focuses on how role of women seen from Muted Group Theory about silencing of women in public interest in movie “At Stake (Pertaruhan)”. This movie consists of four short stories such as Effort for Love, What’s the point?, Miss or Mrs?, The Children’s Fortune.